The Relationship Between Conflict Management Of School Administrators And Morale In Performance Of The Teachers In Schools Under The Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 - Thipsot, Suthathip; Montaisong, Teerawat (Mahachula Academic Journal, 2021)
The purposes of this research were to (1) study the conflict management of school administrators; (2) study the morale in performance of the teachers in schools; (3) The relationship between conflict management of school administrators and morale in performance of the teachers in schools. The samples of this research were 320 teachers under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 who were selected by determining sample size through the Krejcie and Morgan’s table and Stratified sampling. The research instrument used are a five-point-scale questionnaire about conflict management of school administrators with the reliability at 0.90 and morale in performance of the teachers with the reliability at 0.97. The statistics used in this research are percentage, mean, standard deviation and Pearson's correlation coefficient. The results indicate that: (1) as a whole, the conflict management of school administrators is at the moderate level, when considered individually, it was found that the acceptable and conciliatory conflict management with the highest average, followed by cooperative conflict management and the item with the least average is the avoidance of conflict management; (2) as a whole, the morale in performance of the teachers in schools is at a high level, when considering each aspect, it was found that the sense of responsibility with the highest mean, followed by the sense of satisfaction at work and the item with the least mean value is relationships in the organization; (3) The relationship between conflict management of school administrators and morale in performance of the teachers in schools under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 is a positive relatively low level with statistical significance level of .01.